Key takeaways from China's success in eliminating malaria: leveraging existing evidence for a malaria-free world. Issue 4 (29th April 2022) - Feng, Xinyu; Huang, Fang; Yin, Jianhai; Wang, Rubo; Xia, Zhigui
Abstract : Although the total number of malaria cases and fatalities have declined globally since 2010, there were still 241 million malaria cases identified across 85 countries and territories in 2020. As the global malaria eradication process accelerates, more countries have launched their own initiatives of elimination. Notably, China achieved this goal by 2021, ending thousands of years of endemic. Undoubtedly, tremendous experience and vital lessons have been accrued en route to the malaria-free goal in malaria-eliminated countries including China. To enhance prospects of a malaria-free world by bridging the key evidence from a malaria-eliminated country to the contexts of affected, this personal view highlights concerted commitments and universal investment in healthcare, improved surveillance and response system, constant capacity building, demand-oriented scientific research, and multiway cooperation, which have helped China to eliminate this ancient scourge. We discuss how these key takeaways could be leveraged to different contexts. We also argue the long-term challenges and barriers on the pathway to malaria elimination and underline the needs for consistent efforts to maintain zero indigenous cases and prevent re-introduction of malaria. Through concerted efforts from global collaboration, a malaria-free world can become a reality.